Multilevel Analysis of Factors Affecting Depression Risk among the Elderly: Loneliness, Living Status, Physical Activity, Age, Gender, and Education - Emirza Nur Wicaksono; Didik Gunawan Tamtomo; Hanung Prasetya; Bhisma Murti (Journal of Epidemiology and Public Health, 2024)
Background: There is still a high prevalence of depression in the elderly which is affected by loneliness, low physical activity, gender, last education, and residence status. Elderly people who live alone or have lost a life partner are more prone to depression. Although family support and public health services such as Posyandu are expected to protect against the risk of depression, there have not been many studies that have examined in depth the influence of Posyandu as a contextual factor in reducing the risk of depression in the elderly. This study aims to analyze the influence of these factors and the role of Posyandu in reducing the risk of depression.Subjects and Method: This study used a cross-sectional design conducted in 25 Posyandu Elderly in Grogol District, Sukoharjo Regency from August to September 2024. A total of 204 elderly respon-dents aged 60 years and above were selected using Stratified Random Sampling. The dependent variable in this study was depression collected using the PHQ-9 questionnaire, and loneliness was assessed by the UCLA Loneliness Scale. Other independent variables such as physical activity, gender, education, and life status were collected through structured interviews. Multilevel linear regression analysis is used to analyze the relationship between these factors and the risk of depression, taking into account the individual and contextual levels (Posyandu).Results: The average age of the respondents was 66.27 years old (Mean = 66.26, SD = 5.16), with 79.41% of them being female. Loneliness was significantly associated with an increased risk of depression (b= 0.05; CI 95%= 0.07 to 0.10; p=0.024), while living with family reduces the risk of depression (b= -6.33; CI 95%= -8.26 to -4.40; p<0.001). Physical activity did not show a significant association with depression. Gender, education level, and age are also not significant predictors of depression. Contextual speaking, posyandu has no effect as a contextual variable on the variable of depression in the Grogol sub-district (ICC=2.64%).Conclusion: Loneliness is a significant risk factor for depression in the elderly while living with family also reduces the risk of depression in the elderly.